Empowering Youth in the Small-Scale Industry Environment of Bukit Indah: Fostering English and Business Proficiency through Islamic-Based Education - Hasanah, Nurul; Syahban Mada Ali; Andi Adhelya Putri Ramadhani; Iin Dwi Anggereni; Kadaruddin; Sakhmalsyah Bahtiar (Islamic Studies Journal for Social Transformation, 2023)
This research delves into the substantial impact of a Community Service (CS) program that centered on English language acquisition within the unique Small-Scale Industry setting of Bukit Indah. The program ambitiously addressed the prevalent challenge of engaging children in the realm of English education while simultaneously fostering their competence in language proficiency and fundamental business principles. By deploying innovative pedagogical approaches and integrating the principles of Islamic-based education, the program meticulously crafted an interactive and dynamically engaging learning environment. The outcomes were undeniably impressive, as the participating children exhibited noticeable advancements in their language skills, a palpable surge in their enthusiasm for learning, and a solid grounding in the rudiments of business concepts. Furthermore, the initiative delivered invaluable experiential learning opportunities to management students, underpinning the significance of ethical conduct, moral values, and cultural resonance in alignment with Islamic principles.